TOOTH POSITION ANALYSIS DEVICE, TOOTH REGION EXTRACTION MODEL GENERATION METHOD, TOOTH POSITION ANALYSIS METHOD, PROGRAM, AND RECORDING MEDIUM - KOIWA Yoshinori; ONO Takashi; HIGUCHI Kotaro; KOBAYASHI Masaharu; ISHIDA Yuji; SUGA Kazuhiro (2020)
Provided is a new system which can simply analyze tooth position movement. This tooth movement analysis device includes: an input unit that receives input of a three-dimensional CT image of a subject oral cavity and an oral scanner three-dimensional mesh; a tooth region extraction unit that separates the three-dimensional CT image into an X cross section two-dimensional image, a Y cross section two-dimensional image and a Z cross section two-dimensional image, to extract colored two-dimensional images in which a region of a tooth including the tooth crown and the tooth root is color-coded by tooth; a combining unit that generates a color-coded colored three-dimensional image by combining the color-coded colored two-dimensional images; a correction unit that corrects an error in the colored three-dimensional image; a reconstruction unit that reconstructs from the color-coded tooth region in the corrected colored three-dimensional image, the three-dimensional mesh as tooth surface shapes constituted by a collection of three-dimensional coordinate points; and an alignment unit that aligns, on the basis of tooth crown surfaces, the reconstructed reconstruction three-dimensional mesh and the oral scanner three-dimensional mesh, and uses same as positional relationship reference information. La présente invention concerne un nouveau système qui permet d'analyser de manière simple un mouvement de position de dent. Le dispositif d'analyse de mouvement de dent selon l'invention comprend : une unité d'entrée qui reçoit une entrée d'une image de tomodensitométrie en trois dimensions d'une cavité buccale d'un sujet et un maillage en trois dimensions de scanner oral ; une unité d'extraction de région de dent qui sépare l'image de tomodensitométrie en trois dimensions en une image en deux dimensions de section transversale X, une image en deux dimensions de section transversale Y et une image en deux dimensions de section transversale Z, pour extraire des images en deux dimensions colorées dans lesquelles une région d'une dent comprenant la couronne dentaire et la racine dentaire est codée en couleur par dent ; une unité de combinaison qui génère une image colorée en trois dimensions à codage couleur par combinaison des images colorées en deux dimensions codées en couleur ; une unité de correction qui corrige une erreur dans l'image colorée en trois dimensions ; une unité de reconstruction qui reconstruit à partir de la région de dent à codage couleur dans l'image colorée en trois dimensions corrigée, le maillage en trois dimensions comme formes de surface de dent constituées d'une collection de points de coordonnées en trois dimensions ; et une unité d'alignement qui aligne, sur la base des surfaces de couronne dentaire, le maillage de reconstruction en trois dimensions reconstruit et le maillage en trois dimensions de scanner oral, et les utilise comme informations de référence de relation de position. 簡便に歯の位置の変動を分析することができる新たなシステムを提供する。　本発明の歯の移動の分析装置は、対象の口腔の三次元ＣＴ画像とオーラルスキャナ三次元メッシュとを入力する入力部、三次元ＣＴ画像をＸ断面の二次元画像、Ｙ断面の二次元画像、およびＺ断面の二次元画像に分解して、歯冠と歯根とを含む歯の領域が歯ごとに色分けされた着色二次元画像を抽出する歯領域抽出部、色分けされた着色二次元画像を結合して、色分けされた着色三次元画像を生成する結合部、着色三次元画像における誤差を補正する補正部、補正した着色三次元画像における色分けされた歯の領域から、三次元座標点の集合から構成された歯の表面形状として、三次元メッシュを再構築する再構築部、再構築した再構築三次元メッシュとオーラルスキャナ三次元メッシュとを、歯冠表面により位置合わせして位置関係の基準情報とする位置合わせ部を含む。